Haem catabolism: a novel modulator of inflammation in Gilbert's syndrome. (19th July 2013) - Wallner, Marlies; Bulmer, Andrew C.; Mölzer, Christine; Müllner, Elisabeth; Marculescu, Rodrig; Doberer, Daniel; Wolzt, Michael; Wagner, Oswald F.; Wagner, Karl‐Heinz
Abstract Background Moderately elevated unconjugated bilirubin concentrations protect against inflammatory diseases and are present in individuals with Gilbert's syndrome. This study examined the relationship between circulating haem oxygenase catabolites, unconjugated bilirubin, carboxy haemoglobin, iron and inflammatory parameters. Materials and methods Seventy‐six matched individuals were allocated to Gilbert's syndrome (GS) or control group (unconjugated bilirubin ≥ or < 17·1 μM). Iron, carboxy haemoglobin and high‐sensitivity C‐reactive protein were analysed using routine diagnostic tests. Unconjugated bilirubin and haem were analysed using high‐performance liquid chromatography. The cytokines IL‐1β, TNF‐α and IL‐6 were assessed using high‐sensitivity enzyme‐linked immunosorbent assays. Results Gilbert's syndrome subjects had significantly greater levels of unconjugated bilirubin (P < 0·05), carboxy haemoglobin (P < 0·05), iron (P < 0·05), IL‐1β (P < 0·05), a significantly lower body mass index (P < 0·05) and IL‐6 concentrations (P < 0·05) vs. controls. Regression analysis revealed that unconjugated bilirubin mainly explained IL‐1β results (16%), and body mass index+IL‐6 predicted 26% of the variance in C‐reactive protein concentrations. Conclusions A positive relationship between unconjugated bilirubin and free plasma haem, iron and carboxy haemoglobin indicated a positive feedback loop of haem oxygenase induction possibly mediated by unconjugated bilirubin. Furthermore, reduced body mass index in Gilbert's syndrome individuals was linked to reduced inflammation status, which could be influenced by circulating haem oxygenase catabolites and contribute to reduced risk of noncommunicable diseases in this population.